2018
DOI: 10.24326/asphc.2018.4.9
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF Pseudomonas STRAINS AND ARBUSCULAR MYCORRHIZA FUNGI AS ORGANIC PHOSPHATE–SOLUBILIZING IN THE YIELD AND QUALITY IMPROVEMENT OF STRAWBERRY (Fragaria × ananassa Duch., cv. Selva) FRUIT

Abstract: This study evaluated the effect of Pseudomonas strains and arbuscular mycorrhiza fungi (AMF) in enhancing strawberry yield and phenolic and antioxidant capacity on a phosphorus (P) deficient calcareous soil. The experiments were conducted in three replicates with six treatments (four Pseudomonas strains, AMF and control) and three rates of P-fertilizer (0, 75, 150 kg P ha-1). Application of higher phosphate rates decreased total antioxidant capacity, total phenolic and flavonols content, whereas AMF and Pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…However, single inoculation of AMF and Pseudomonas species increased grain yield but the highest rates were observed in co-inoculated plants and their synergetic impact on grain yield and yield components was remarkable. These findings are same to that of Espidkar et al (2017), Viollet et al (2017) and Ansari et al (2018). They demonstrated that colonization of AMF helper bacteria such as Pseudomonas, adhere to the root surface and improve AMF-plant symbiosis relations.…”
Section: Harvest Indexsupporting
confidence: 76%
See 2 more Smart Citations
“…However, single inoculation of AMF and Pseudomonas species increased grain yield but the highest rates were observed in co-inoculated plants and their synergetic impact on grain yield and yield components was remarkable. These findings are same to that of Espidkar et al (2017), Viollet et al (2017) and Ansari et al (2018). They demonstrated that colonization of AMF helper bacteria such as Pseudomonas, adhere to the root surface and improve AMF-plant symbiosis relations.…”
Section: Harvest Indexsupporting
confidence: 76%
“…Based on the findings of Ruiz-Lozano et al (2012), during the salt stress, AMF symbiosis exerts vast morphologic changes in rice that provides it for salt tolerance and the majority of these changes these changes concern vacuolar or cytoplasmic membrane systems. Ansari et al (2018) reported that under drought stress, plants with higher heights may increase final grain weight and yield during the grain filling by remobilization process. On the other hands, rice grain yield is a function of different components like fertile tiller number, panicle number, grain number and grain weight so, impact of treatments on grain yield is defined by impacting on yield components.…”
Section: Harvest Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did not observe any effect of the fungi on the TSS/TA ratio in the fruit. In a study by Ansari et al (2018), a marked increase in TSS and TA was observed in mycorrhizal strawberry plants grown under phosphorus deficiency. In the present study, a negative impact of Rhizocell C on the TSS content of strawberry fruit was observed.…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that the fruits harvested in the early period of the successive harvested fruit species are superior in terms of pomological properties; while the fruit flesh hardness and phytochemical characteristics are at lower levels (Zorenc et al, 2016). Moreover, these fruits are not suitable for storage due to their high pectinase enzyme activity and respiration rate (Erkan and Pekmezci, 2004;Ali et al, 2018;Ansari et al, 2018). Moreover, this situation will be opposite if the harvesting period is extended and continued.…”
Section: Introductionmentioning
confidence: 99%